Decreased expression of neuropilin-1 as a novel key factor contributing to peripheral microvasculopathy and defective angiogenesis in systemic sclerosis. Issue 8 (10th September 2015) - Romano, Eloisa; Chora, Inês; Manetti, Mirko; Mazzotta, Celestina; Rosa, Irene; Bellando-Randone, Silvia; Blagojevic, Jelena; Soares, Raquel; Avouac, Jerôme; Allanore, Yannick; Ibba-Manneschi, Lidia; Matucci-Cerinic, Marco; et al.
Abstract : Objectives: In systemic sclerosis (SSc), vascular involvement is characterised by vascular endothelial growth factor (VEGF)-A/VEGF receptor (VEGFR) system disturbances. Neuropilin-1 (NRP1), a receptor for both class-3 semaphorins (Sema3s) and VEGF-A, is required for optimal VEGF-A/VEGFR-2 signalling. Here, we investigated the possible involvement of Sema3A/NRP1 axis in SSc. Methods: Circulating Sema3A and soluble NRP1 (sNRP1) were measured in patients with SSc and controls. NRP1 and Sema3A expression in skin biopsies was evaluated by immunofluorescence and western blotting. NRP1 expression was assessed in SSc and healthy dermal microvascular endothelial cells (SSc-MVECs and H-MVECs), and in SSc and control endothelial progenitor cell (EPC)-derived endothelial cells (ECs). The possible impact of transcription factor Friend leukaemia integration 1 (Fli1) deficiency on endothelial NRP1 expression was investigated by gene silencing. The binding of Fli1 to NRP1 gene promoter was evaluated using chromatin immunoprecipitation. Capillary morphogenesis was performed on Matrigel. Results: Decreased sNRP1 levels in SSc were associated with active and late nailfold videocapillaroscopy patterns and digital ulcers. No difference in Sema3A was found between patients and controls. NRP1 was significantly decreased in SSc-MVECs both ex vivo and in vitro. NRP1 and Fli1 significantly decreased in H-MVECs challenged with SSc sera, while they were not different in SSc and control EPC-derived ECs. Fli1 occupied the NRP1 gene promoter and Fli1 gene silencing reduced NRP1 expression in H-MVECs. NRP1 gene silencing in H-MVECs resulted in a significantly impaired angiogenic capacity comparable to that of cells treated with SSc sera. Conclusion: In SSc, NRP1 deficiency may be an additional factor in the perturbed VEGF-A/VEGFR-2 system contributing to peripheral microvasculopathy and defective angiogenesis.